Penggunaan Media Pembelajaran Aplikasi Quizizz pada Masa Pandemi Di SMK N 5 Palembang - Kushendratno, Kushendratno (Yayasan Sembilan Pemuda Indonesia, 2021)
This article aims to illustrate how to use Quizizz as a learning tool. This article is a study of the literature, including references to books, journals, and Internet postings. This article explores how the Quizizz application can generate creative, innovative, and interesting learning media, and why educators should use it as a learning tool, particularly during the pandemic of Covid-19.